Amyloid-β fosters p35/CDK5 signaling contributing to changes of inhibitory synapses in early stages of cerebral amyloidosis - Kiss, Eva; Groeneweg, Femke; Gorgas, Karin; Schlicksupp, Andrea; Kins, Stefan; Kirsch, Joachim; Kuhse, Jochen (Journal of Alzheimer's disease, 2020)
Early changes in inhibitory synapse connectivities are thought to contribute to the excitation/inhibition imbalance preceding neurodegeneration in Alzheimer’s disease (AD). Recently, we reported a robust increase in the level of different key-proteins of inhibitory synapses in hippocampal subregions of pre-symptomatic APPswe-PS1 mice, a model of cerebral amyloidosis. Besides increased inhibitory synaptic clusters on parvalbumin-positive projections in CA1 and CA3, we observed impaired communication between these two hippocampal areas of young APP-PS1 mice. Interestingly, the phosphorylation of gephyrin, a major organizer of inhibitory synapses, was also increased. Here, we demonstrate that the protein levels of CDK5, a kinase involved in the phosphorylation of gephyrin, and its regulatory protein p35 are also significantly increased in hippocampal subregions of young APP-PS1 mice. Consistently, the expression of hAPP-swe in cultured hippocampal neurons resulted in higher p35-protein levels, indicating a possible molecular link between increased Aβ-production and the elevated p35/CDK5 levels seen in vivo. Further, a shRNA mediated downregulation of p35-expression in hippocampal neurons correlated with a decrease in gephyrin phosphorylation and in a reduced density of synaptic γ2-GABAA-receptor clusters. These findings, together with the detection of gephyrin colocalization with CDK5 and p35 by immunostaining and proximity ligation experiments in vivo and in vitro, are supporting our hypothesis that Aβ has a profound impact on inhibitory network properties, likely mediated at least in part by p35/CDK5 signaling. This further underscores the impact of altered inhibitory synaptic transmission in AD.